Nuclear Accumulation of Mutated β-Catenin in Hepatocellular Carcinoma Is Associated with Increased Cell Proliferation - Nhieu, Jeanne Tran Van (American Society for Investigative Pathology, 1999)
Inappropriate activation of the Wnt pathway resulting from β-catenin gene alterations has recently been implicated in the development of hepatocellular carcinoma (HCC). To explore the in vivo effects of mutated β-catenin, HCC specimens from 32 patients carrying one or several tumors were screened for somatic mutations in exon 3 of the β-catenin gene, and the expression and subcellular localization of β-catenin was studied by immunohistochemistry. Missense mutations or interstitial deletions in β-catenin exon 3 were detected in 12 of 35 (34%) HCC samples. After immunostaining, most tumors exhibited increased membranous and/or cytoplasmic expression of β-catenin compared with adjacent nontumoral liver. Strong nuclear accumulation of β-catenin was observed either focally or uniformly in 15 of 35 (43%) tumor specimens, but not in cirrhotic nodules or dysplastic liver cells in adjacent liver. Aberrant nuclear expression of β-catenin was significantly associated with the presence of mutations in the β-catenin gene (P < 0.005). Moreover, nuclear β-catenin staining correlated significantly with increased Ki-67 proliferative index in tumor (P < 0.001) and seemed to be associated with poor outcome in patients with HCC. In conclusion, our data indicate that activation of the Wnt/β-catenin pathway in HCC results mainly from somatic mutations in the β-catenin gene and may promote tumor progression by stimulating tumor cell proliferation.